2005
DOI: 10.1179/108331905x43454
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of techniques to enhance peak cough flow and maintain vital capacity in neuromuscular disease: the case for mechanical insufflation–exsufflation

Abstract: Patients with neuromuscular disease risk developing chest infections due to the inability to cough effectively and to maintain adequate lung volume. This systematic review aimed to evaluate the comparative effectiveness of techniques used in the respiratory management of these patients. Articles evaluating peak cough flow measurements and maintenance of lung volumes only were selected to retain a specific focus for comparison. A database search was performed using the Cochrane controlled register, AMED, Cinahl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Independent airway clearance techniques are ineffective in patients with compromised respiratory muscles. Conventional techniques such as postural drainage are unlikely to be effective in this client group,340 and suction is neither well tolerated nor therefore successful 325 330 340 342. Thus patients with compromised respiratory muscles require assisted coughing, non-invasive assistance and aids for airway clearance.…”
Section: Section 6 Neuromuscular Diseases and Musculoskeletal Disordementioning
confidence: 99%
See 1 more Smart Citation
“…Independent airway clearance techniques are ineffective in patients with compromised respiratory muscles. Conventional techniques such as postural drainage are unlikely to be effective in this client group,340 and suction is neither well tolerated nor therefore successful 325 330 340 342. Thus patients with compromised respiratory muscles require assisted coughing, non-invasive assistance and aids for airway clearance.…”
Section: Section 6 Neuromuscular Diseases and Musculoskeletal Disordementioning
confidence: 99%
“…For a fuller description, please see the section with this title under Spinal cord injury. A systematic review of mechanical in-exsufflation342 includes three controlled trials comparing mechanical in-exsufflation with other assisted cough techniques in mixed stable patient populations with neuromuscular disease 333 335 358. Two of these studies335 358 found that the mean peak cough flow of included subjects increased to levels greater than the 270 l/min stable threshold, which was not the case for the third 333…”
Section: Section 6 Neuromuscular Diseases and Musculoskeletal Disordementioning
confidence: 99%
“…This is the first systematic review including observational studies and the first literature update available on MI-E devices used for airway clearance in patients with neuromuscular disease since the work of Anderson et al 27 in 2005. Our review underlines the lack of robust data on MI-E use for airway clearance in neuromuscular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of MI-E devices in Europe since 2002 has increased the number of studies initiated. 25,26 The first team that performed a systematic review on MI-E was Anderson et al 27 in 2005. Their systematic review included 4 controlled trials, with a total of 98 subjects with neuromuscular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, high MI-E pressure settings have generally been considered to be most effective for neuromuscular patients, 34,35 and most studies and clinicians apply settings of Ϯ 40 cm H 2 O or higher. [36][37][38] Our findings indicate that in ALS, high pressures were the most provocative and most likely to cause adverse responses, and that such responses were difficult to predict based on other clinical signs or symptoms. Based on these observations, treatment pressures as high as 50 cm H 2 O should probably be avoided in challenging cases of ALS, especially if fiberoptic laryngoscopy is not available.…”
Section: Treatment Pressuresmentioning
confidence: 92%